PEMBELAJARAN MENULIS CERITA PENDEK MELALUI METODE MIND MAPPING - Sari, Lela; Wikanengsih, Wikanengsih; Fauziya, Diena San (Parole (Jurnal Pendidikan Bahasa dan Sastra Indonesia), 2020)
This research is to study the learning of writing short stories through mind mapping methods in class XI students of SMK HAMKA Cikande. Learning to write short stories in fact reap various problems and are still less attractive to students, among them, the difficulty of students to start the writing process, the difficulties of students to develop ideas thinking, and writing as difficult and less interesting things. This study aims to describe learning to write short stories through mind mapping methods that will overcome students 'difficulties in writing, help students find ideas, and to open students' minds in mapping ideas. This research method uses descriptive qualitative which aims to make a description naturally through objects accurately, factually and systematically. The results showed students get an average score of 49 initial tests and final tests get an average score of 79. For the sake of learning, learning to write short stories through the mind mapping method has increased very well.